Health workforce and governance: the crisis in Nigeria - Davies Adeloye; Rotimi Adedeji David; Adenike Ayobola Olaogun; Asa Auta; Adedapo Adesokan; Muktar Gadanya; Jacob Kehinde Opele; Oluwafemi Owagbemi; Alexander Iseolorunkanmi (BMC, 2017)
Abstract Background In Nigeria, several challenges have been reported within the health sector, especially in training, funding, employment, and deployment of the health workforce. We aimed to review recent health workforce crises in the Nigerian health sector to identify key underlying causes and provide recommendations toward preventing and/or managing potential future crises in Nigeria. Methods We conducted a scoping literature search of PubMed to identify studies on health workforce and health governance in Nigeria. A critical analysis, with extended commentary, on recent health workforce crises (2010-2016) and the health system in Nigeria was conducted. Results The Nigerian health system is relatively weak, and there is yet a coordinated response across the country. A number of health workforce crises have been reported in recent times due to several months' salaries owed, poor welfare, lack of appropriate health facilities and emerging factions among health workers. Poor administration and response across different levels of government have played contributory roles to further internal crises among health workers, with different factions engaged in protracted supremacy challenge. These crises have consequently prevented optimal healthcare delivery to the Nigerian population. Conclusions An encompassing stakeholders' forum in the Nigerian health sector remain essential. The national health system needs a solid administrative policy foundation that allows coordination of priorities and partnerships in the health workforce and among various stakeholders. It is hoped that this paper may prompt relevant reforms in health workforce and governance in Nigeria toward better health service delivery in the country.